2006 IEEE International Conference on Multimedia and Expo 2006
DOI: 10.1109/icme.2006.262792
|View full text |Cite
|
Sign up to set email alerts
|

Steganalysis based on Markov Model of Thresholded Prediction-Error Image

Abstract: A steganalysis system based on 2-D Markov chain of thresholded prediction-error image is proposed in this paper. Image pixels are predicted with their neighboring pixels, and the prediction-error image is generated by subtracting the prediction value from the pixel value and then thresholded with a predefined threshold. The empirical transition matrixes of Markov chain along the horizontal, vertical and diagonal directions serve as features for steganalysis. Support vector machines (SVM) are utilized as classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 9 publications
(19 reference statements)
0
49
0
Order By: Relevance
“…It was then further improved to model pixel differences instead of pixel values in [26]. In our paper, we show that there is a great performance benefit in using higher-order models without running into the curse of dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…It was then further improved to model pixel differences instead of pixel values in [26]. In our paper, we show that there is a great performance benefit in using higher-order models without running into the curse of dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…Steganalyzers working with features formed as joint or transition probability distributions as features were shown to outperform [27,25,12,11,13] all previously proposed attacks on LSB matching and the content-adaptive HUGO. In summary, it makes perfect sense to expect that the accuracy of the WS detector can be improved as well by considering higher-order statistical constructs from the residual.…”
Section: Motivationmentioning
confidence: 99%
“…For such embedding operations, the most accurate detectors today are built as classifiers using features obtained as sampled joint distributions (co-occurrence matrices) among neighboring elements of noise residuals [12,11,27,25,13]. These detectors perform equally well for both LSB replacement and LSB matching because features formed from noise residuals are generally blind to pixels' parity.…”
mentioning
confidence: 99%
“…In (Zou et al, 2006), the authors have suggested steganalysis scheme which depends on a 2-D Markov chain thresholded forecast-error image. Image pixels are forecasted with their adjacenting pixels, and the forecast-error image is produced by decreasing the calculated value of the pixel value and then thresholded with a predefined threshold.…”
Section: Support Vector Machine Classification (Svm)mentioning
confidence: 99%
“…(http://www.datahiding.org), courtesy of Dr. Edward Delp, Purdue University 1000 WAV audio signals files covering different types such as digital speech, on-line broadcast, and music, etc. 19 (Zou et al, 2006) Used 2812 images download from the website of Vision Research Lab, University of California, Santa Barbara. …”
mentioning
confidence: 99%